The Role of Health Promotion Hospital in Fulfilling Patient and Family Right in RA. Basoeni Hospital, Mojokerto - Rizka Lina Manfaati; Oedojo Soedirham; Rika Subarniati Triyoga; Ardi Bastian (Health Notions, 2018)
-